Device with controllable liquid drop transportation path and preparation method thereof

By using the structure, magnetic control layer, and lubricating layer in the controlling device of the droplet transportation path, the magnetic control layer and silicon oil of the virtual graphene-tetraxide triangle binding are used to solve the existing technology The problem of complex preparation methods and insufficient accuracy of the hydraulic transmission path realizes high -precision droplet control.

CN119368253AActive Publication Date: 2025-01-28GUANGDONG UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411522182.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The preparation method of existing droplet transport path controllable devices is complex, and the droplet transport path is insufficient, making it difficult to meet the application needs of high precision.

Method used

Adopt a device preparation method including the base, magnetic control layer, and lubrication layer, the base surface covers the mask and naked area, and the naked area is an equal waist triangle. The magnetic control layer, and the lubricating layer is deposited on the base surface.

Benefits of technology

The accurate and flexible control of the droplet transmission path is achieved, ensuring the controllability and accuracy of the droplet transportation path, simplifying the preparation process and reducing the cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368253A_ABST
    Figure CN119368253A_ABST
Patent Text Reader

Abstract

The invention discloses a device with a controllable liquid drop transportation path and a preparation method thereof. The preparation method comprises the following steps: A, partially covering the surface of a substrate with a mask; b, preparing a ferric trichloride-carbon base-fluorine source compound; c, smearing the ferric trichloride-carbon base-fluorine source compound obtained in the step B on the surface of the exposed area of the substrate obtained in the step A to obtain the substrate with the ferric trichloride-carbon base-fluorine source compound attached to the surface; d, the ferric trichloride-carbon base-fluorine source compound on the surface of the substrate in the step C is processed, and the substrate with the fluorine-doped graphene-ferroferric oxide compound attached to the surface is obtained; e, the mask on the surface of the substrate in the step D is removed and cleaned, and the substrate with a magnetic control layer is obtained; and F, depositing a lubricating layer on the surface of the substrate with the magnetic control layer to obtain the device with the controllable liquid drop transportation path. According to the preparation method of the device with the controllable liquid drop transportation path, provided by the invention, the prepared device can ensure the controllability and the accuracy of the liquid drop transportation path.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microfluidic technology, and in particular to a device with a controllable droplet transport path and a preparation method thereof. Background Art

[0002] Precision manipulation of droplets is a cutting-edge technology involving multiple fields such as microfluidics, surface science, materials science and control engineering. It covers the precise movement, positioning and manipulation of tiny droplets on solid surfaces, providing indispensable technical support for multiple key fields such as microfluidics, biomedical research and chemical industry.

[0003] In order to achieve fine control over droplet transport, multi-point parallelism and path manipulation, researchers have developed a variety of devices with controllable droplet transport paths. These devices mainly rely on electric field, magnetic field manipulation and surface tension regulation to control the movement of droplets. However, as the application field continues to increase the complexity and precision of droplet manipulation, these devices have gradually shown the following limitations: (1) Traditional magnetic materials such as silicon steel and nickel-iron alloys are prone to lose their magnetism in high temperature environments, limiting their application in high-temperature working environments; (2) Traditional magnetic materials such as silicon steel and nickel-iron alloys lack magnetic directivity in the initial state and are unevenly distributed. They require additional magnetization steps to obtain controllable magnetic response, but this process often leads to a decrease in magnetic field control accuracy, making it difficult to maintain stable control of droplets during movement, thereby affecting the precise control of the transport path; (3) The preparation process of the above devices usually involves multiple tedious steps such as film formation, curing, patterning and magnetization, which not only increases the complexity and cost of the preparation method, but also makes it difficult to ensure the uniformity and stability of the magnetic material, further affecting the accuracy of the droplet transport path.

[0004] In order to overcome the above limitations, the Chinese invention patent with publication number CN115386110A proposed a flexible film with controllable droplet transport path using silica gel as a flexible matrix, which forms a wettability gradient by constructing obvious rough areas and smooth areas, thereby achieving droplet control. However, this film is mainly suitable for simple droplet movement and separation tasks. When faced with the need for high-precision droplet control, the accuracy of its droplet transmission path is still insufficient.

[0005] In summary, the current methods for preparing devices with controllable droplet transport paths generally face problems such as complex preparation methods and limited accuracy of droplet transport paths, and are still difficult to meet actual usage requirements. Summary of the invention

[0006] The first purpose of the present invention is to propose a method for preparing a device with a controllable droplet transport path, which method not only simplifies the preparation process and improves production efficiency, but also the prepared device can accurately control the droplets and flexibly and stably transport them, ensuring the controllability and accuracy of the droplet transport path, thereby effectively overcoming the problems of complex preparation methods and insufficient accuracy of droplet transport paths in the prior art.

[0007] The second purpose of the present invention is to propose a device with controllable droplet transport path prepared by the above-mentioned preparation method with controllable droplet transport path, which can achieve the controllability and accuracy of the droplet transport path and greatly meet the actual application needs.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] A method for preparing a device with a controllable droplet transport path comprises the following steps:

[0010] A. Covering a part of the surface of the substrate with a mask; wherein the surface of the substrate includes a mask-covered area and an exposed area, the exposed area is in the shape of an isosceles triangle, and a plurality of the isosceles triangles are arranged in an interlaced and equidistant manner, and the substrate is made of a high-temperature resistant non-magnetic material;

[0011] B. dissolving anhydrous ferric chloride in deionized water and stirring to obtain a ferric chloride solution; mixing the ferric chloride solution with a carbon-based raw material and a fluorine source raw material to obtain a ferric chloride-carbon-based-fluorine source composite;

[0012] C. applying the ferric chloride-carbon-based-fluorine source composite of step B evenly to the surface of the exposed area of ​​the substrate in step A to obtain a substrate with the ferric chloride-carbon-based-fluorine source composite attached to the surface;

[0013] D. processing the ferric chloride-carbon-based-fluorine source complex on the surface of the substrate in step C by using a pulse current to obtain a substrate with a fluorine-doped graphene-ferroferric oxide complex attached to the surface;

[0014] E. removing the mask on the surface of the substrate in step D and cleaning it to obtain a substrate having a magnetron layer; wherein the magnetron layer is a fluorine-doped graphene-ferroferric oxide combination;

[0015] F. Immerse the substrate with the magnetron layer in step E in silicone oil, take it out and suspend it for standing, and then deposit a lubricating layer on the surface of the substrate with the magnetron layer to obtain a device with a controllable droplet transport path.

[0016] Furthermore, in step A, the vertex angle of the isosceles triangle is 20 to 45 degrees.

[0017] Furthermore, in step B, calculated by mass ratio, the mixing ratio of the anhydrous ferric chloride to the deionized water is (0.9-1.1):2.

[0018] Furthermore, in step B, calculated by mass ratio, the mixing ratio of the ferric chloride solution, the carbon-based raw material and the fluorine source raw material is (0.45-0.55):1:(0.1-0.12).

[0019] Furthermore, in step D, the voltage of the pulse current is 120-140V, the current is 180-200A, and the processing time is 8-10s.

[0020] Furthermore, in step E, the thickness of the magnetron layer is 0.3-0.5 mm.

[0021] Furthermore, in step F, the soaking time is 4 to 6 minutes; and the hanging and standing time is 10 to 15 minutes.

[0022] Furthermore, in step A, the substrate includes any one of a glass substrate, a silicon wafer and an alumina ceramic.

[0023] Further, in step B, the carbon-based raw material includes any one or more combinations of carbon black, coal powder, lignin and corn silk;

[0024] The fluorine source raw material includes any one of fluorinated graphite, perfluorooctanoic acid, perfluorohexyl sulfonic acid and polytetrafluoroethylene.

[0025] A device with a controllable droplet transport path is prepared using the above-mentioned method for preparing a device with a controllable droplet transport path.

[0026] The technical solution provided by the present invention may include the following beneficial effects:

[0027] 1. The device prepared by the present technical solution includes a substrate, a magnetron layer and a lubricating layer distributed from bottom to top, and the composition of the magnetron layer is a fluorine-doped graphene-iron tetroxide combination. The iron tetroxide in the magnetron layer gives the device excellent magnetic properties. Under the action of an external magnetic field, the magnetic domains of the iron tetroxide will be rearranged in an orderly manner; and the high mechanical strength of graphene ensures the stability of the device structure. Therefore, when the magnetic domains of the iron tetroxide are rearranged, the surface of the magnetron layer only shows dynamic changes in the microstructure, that is, the micro-roughness and surface energy of the area close to the magnetic field on the surface of the device are significantly improved, while the area away from the magnetic field maintains the original smooth state and low surface energy, thereby forming a dual effect of surface energy gradient and micro-roughness gradient on the surface of the device. When a droplet is placed in an area with high micro-roughness and large surface energy, thanks to the above-mentioned gradient effect, the droplet will spontaneously migrate to an area with low surface energy and smooth surface, realizing accurate and flexible control of the droplet transmission path. At the same time, the stronger the external magnetic field, the higher the microscopic roughness and surface energy of the area close to the magnetic field. When the direction of droplet transmission needs to be changed, the direction of the external magnetic field can be changed to achieve the adjustment of the droplet transmission direction. Therefore, based on the above principle, the transmission of droplets on the device surface can be achieved by applying an external magnetic field and adjusting the strength and direction of the magnetic field.

[0028] 2. In order to further improve the controllability and accuracy of the droplet transmission path, the surface of the substrate of the present technical solution includes a mask-covered area and an exposed area. The shape of the exposed area is an isosceles triangle, and multiple isosceles triangles are staggered and arranged at equal intervals. The exposed area is used as a patterned template, which can accurately replicate its shape to the magnetic control layer, so that the outer surface of the device presents a unique shape with alternating vertex corners and bottom edges. When the droplet is transmitted to the vertex, the surface energy caused by its sharp shape increases sharply, becoming a powerful driving force for driving the droplet to gradually migrate to the adjacent bottom edge, making the droplet easy to be guided and smoothly jump from the current vertex to the adjacent bottom edge. In addition, the unique shape of the alternating vertex corners and bottom edges on the outer surface of the device has a natural geometric guidance. When the droplet is driven by the surface energy gradient in the bottom area, the droplet is more inclined to move to the adjacent vertex area. The above two aspects cooperate with each other, which is conducive to improving the controllability and accuracy of the droplet transmission path and meeting actual usage needs.

[0029] 3. If the material of the substrate is magnetic, it will interfere with the effect of the external magnetic field, affecting the manipulation of the droplets, thereby affecting the accuracy and controllability of the droplet transmission path; in addition, a high temperature environment will be generated during the pulse current processing process. If the material of the substrate has poor high temperature resistance, thermal expansion or material deformation may occur, thereby destroying the device structure. Therefore, in this technical solution, the material of the substrate is limited to a non-magnetic and high temperature resistant material, so as to ensure the integrity of the device structure and the accuracy and controllability of the droplet transmission path. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of the structure of a device with a controllable droplet transport path according to the present invention.

[0031] Figure 2 It is a path diagram of the droplets of the present invention being transported on the surface of a device with a controllable droplet transport path.

[0032] Figure 3 It is a schematic diagram of a micro-knife-shaped structure in the prior art in which the exposed area is exposed.

[0033] Figure 4 It is a schematic diagram of a dumbbell-shaped structure in which the exposed area is pointed and thin in the prior art.

[0034] Among them: substrate 1, magnetron layer 2, lubricating layer 3. DETAILED DESCRIPTION

[0035] The present technical solution provides a method for preparing a device with a controllable droplet transport path, comprising the following steps:

[0036] A. Covering a part of the surface of the substrate with a mask; wherein the surface of the substrate includes a mask-covered area and an exposed area, the exposed area is in the shape of an isosceles triangle, and a plurality of the isosceles triangles are arranged in an interlaced and equidistant manner, and the substrate is made of a high-temperature resistant non-magnetic material;

[0037] B. dissolving anhydrous ferric chloride in deionized water and stirring to obtain a ferric chloride solution; mixing the ferric chloride solution with a carbon-based raw material and a fluorine source raw material to obtain a ferric chloride-carbon-based-fluorine source composite;

[0038] C. applying the ferric chloride-carbon-based-fluorine source composite of step B evenly to the surface of the exposed area of ​​the substrate in step A to obtain a substrate with the ferric chloride-carbon-based-fluorine source composite attached to the surface;

[0039] D. processing the ferric chloride-carbon-based-fluorine source complex on the surface of the substrate in step C by using a pulse current to obtain a substrate with a fluorine-doped graphene-ferroferric oxide complex attached to the surface;

[0040] E. removing the mask on the surface of the substrate in step D and cleaning it to obtain a substrate having a magnetron layer; wherein the magnetron layer is a fluorine-doped graphene-ferroferric oxide combination;

[0041] F. Immerse the substrate with the magnetron layer in step E in silicone oil, take it out and suspend it for standing, and then deposit a lubricating layer on the surface of the substrate with the magnetron layer to obtain a device with a controllable droplet transport path.

[0042] In order to overcome the problems of complex preparation methods and limited accuracy of droplet transmission paths in the prior art, this technical solution proposes a method for preparing a device with controllable droplet transport paths, including six steps: A (preparing a substrate with a mask partially covered on the surface), B (preparing a ferric chloride-carbon-based-fluorine source composite), C (applying the composite), D (pulse current processing), E (removing the mask) and F (silicone oil immersion). By designing the surface of the substrate and selecting the substrate material, the prepared device can accurately control the droplets and flexibly and stably transmit them, ensuring the controllability and accuracy of the droplet transmission path. At the same time, compared with the traditional technology involving multiple complex processes such as film formation, curing, patterning and magnetization, this solution abandons the film formation and curing steps, and only requires pulse current processing to form a magnetic control layer in one step, and thanks to the high magnetic properties of ferroferric oxide, no additional magnetization step is required. The simplification of the above two aspects not only reduces the preparation cost, but also enhances the controllability and flexibility of the operation, which is conducive to the industrialization and large-scale production of the product.

[0043] Specifically, the device prepared by the technical solution includes a substrate, a magnetron layer and a lubricating layer (such as Figure 1 As shown), and the composition of the magnetron layer is a fluorine-doped graphene-iron tetroxide combination. The iron tetroxide in the magnetron layer gives the device excellent magnetic properties. Under the action of an external magnetic field, the magnetic domains of the iron tetroxide will be rearranged in an orderly manner; and the high mechanical strength of graphene ensures the stability of the device structure. Therefore, when the magnetic domains of the iron tetroxide are rearranged, the surface of the magnetron layer only shows dynamic changes in the microstructure, that is, the micro-roughness and surface energy of the area close to the magnetic field on the surface of the device are significantly improved, while the area away from the magnetic field maintains the original smooth state and low surface energy, thereby forming a dual effect of surface energy gradient and micro-roughness gradient on the surface of the device. When a droplet is placed in an area with high micro-roughness and large surface energy, thanks to the above-mentioned gradient effect, the droplet will spontaneously migrate to an area with low surface energy and smooth surface, realizing accurate and flexible control of the droplet transmission path. At the same time, the stronger the external magnetic field, the higher the microscopic roughness and surface energy of the area close to the magnetic field. When the direction of droplet transmission needs to be changed, the direction of the external magnetic field can be changed to achieve the adjustment of the droplet transmission direction. Therefore, based on the above principle, the transmission of droplets on the device surface can be achieved by applying an external magnetic field and adjusting the strength and direction of the magnetic field.

[0044] Furthermore, although the transfer of droplets on the device surface can be achieved by applying an external magnetic field and adjusting the strength and direction of the magnetic field, the droplet transfer path (such as Figure 2In order to further improve the controllability and accuracy of the droplet transmission path, the surface of the substrate of the technical solution includes a mask-covered area and an exposed area. The exposed area is in the shape of an isosceles triangle, and multiple isosceles triangles are staggered and arranged at equal intervals (such as Figure 2 As shown, the black area is the area coated with the ferric chloride-carbon-based-fluorine source composite), and the exposed area is used as a patterned template to accurately replicate its morphology to the magnetic control layer, so that the outer surface of the device presents a unique morphology in which the top corners and bottom edges are alternately arranged. When the droplets are transferred to the top corners, the surface energy caused by their sharp morphology increases sharply, which becomes a powerful driving force for driving the droplets to gradually migrate to the adjacent bottom edges, making it easy to guide the droplets and smoothly jump from the current top corner to the adjacent bottom edge. In addition, the unique morphology of the alternating top corners and bottom edges of the outer surface of the device has a natural geometric guidance. When the droplets are driven by the surface energy gradient in the bottom edge area, the droplets tend to move to the adjacent top corner area. The above two effects cooperate with each other, which is conducive to improving the controllability and accuracy of the droplet transmission path and meeting actual usage needs.

[0045] It should be noted that, when the droplet is transferred to the top corner, the surface energy caused by its sharp shape increases sharply, so that the droplet can be transferred from the current top corner to the adjacent bottom edge by the high surface energy of the top corner itself without the need for an external magnetic field. That is, the technical solution can also guide the transfer of the droplet from the current top corner to the adjacent bottom edge by the high surface energy of the top corner itself, and transfer the droplet from the current bottom edge to the next adjacent top corner by an external magnetic field, thereby improving the flexibility of the droplet transfer method.

[0046] Furthermore, the surface energy difference and natural guiding effect of the top corner area of ​​the outer surface of the device make the droplets easy to be guided and transported, and the wider shape of the bottom edge area of ​​the outer surface of the device provides a stable transmission path for the droplets, which is conducive to forming a directional and controllable droplet movement trajectory, thereby ensuring the continuity and stability of droplet manipulation, and supporting the synchronous transmission of multiple droplets and the planning of complex paths. At the same time, the droplets are easy to be guided and transported in the top corner area, and the characteristics of easy stable transmission in the bottom edge area also bring higher flexibility to droplet manipulation, making the device of this technical solution suitable for a variety of liquid types and a wide range of application scenarios, such as precise liquid flow control in microfluidic systems, cell culture array preparation in the biomedical field, and precise reactions and separation processes in chemical synthesis. In addition, since this technical solution controls the movement of droplets through the dual effects of surface energy gradient and microscopic roughness gradient and the guiding effect of the top corner area, compared with the prior art that constructs obvious rough areas and smooth areas, this technical solution has higher control accuracy and more stable transmission of droplets.

[0047] More specifically, ferric chloride itself is a solid. When it is directly mixed with a carbon-based raw material and a fluorine source carbon-based raw material, it is easy to cause uneven mixing. Therefore, the technical solution first prepares a ferric chloride solution before the coating step, and evenly mixes the ferric chloride solution with the carbon-based raw material and the fluorine source raw material to obtain a ferric chloride-carbon-based-fluorine source complex. The ferric chloride-carbon-based-fluorine source complex is then evenly coated on the surface of the exposed area of ​​the substrate in step A to obtain a substrate with the ferric chloride-carbon-based-fluorine source complex attached to the surface, so that the ferric chloride-carbon-based-fluorine source complex on the surface of the substrate can be processed conveniently using a pulse current, thereby further simplifying the preparation method.

[0048] Secondly, the ferric chloride-carbon-based-fluorine source complex on the surface of the substrate in step C is processed by pulse current. The instantaneous high temperature generated by the pulse current causes the ferric chloride solution to instantly change from liquid phase to gas phase and diffuse, and the gas phase ferric chloride undergoes an oxidation-reduction reaction in this process to generate gas phase ferric oxide. When the gas phase ferric oxide contacts the surface of the substrate with a lower temperature, it will condense and deposit on the surface of the substrate to form ferric oxide particles, and due to the uniformity of diffusion, the deposited ferric oxide particles are evenly distributed on the surface of the substrate; at the same time, the instantaneous high temperature generated by the pulse current can also process carbon-based raw materials, because the elements contained in carbon-based raw materials are mainly carbon, nitrogen and oxygen, and The temperature of pulse current processing is relatively high. During the pulse current processing, the bonds between atoms or molecules of carbon-based raw materials are interrupted and converted into carbon dioxide, carbon monoxide, nitrogen dioxide, nitric oxide and graphene. Among them, carbon dioxide, carbon monoxide, nitrogen dioxide and nitric oxide enter the air in the form of gas, and only graphene remains in the final processing product. In this process, the fluorine source can be further incorporated into the graphene through diffusion and penetration to form fluorine-doped graphene, and the fluorine-doped graphene is then tightly combined with the ferroferric oxide particles to form a fluorine-doped graphene-ferroferric oxide combination.

[0049] It should be noted that in conventional technology, the exposed area on the substrate surface is generally designed to be in the shape of a micro-knife (e.g. Figure 3 The black area in the middle) or the dumbbell shape with a thin tip (as shown in Figure 4As shown in the black area in the middle, the above design uses the template effect to make the device surface also present the corresponding shape characteristics. However, the above-mentioned sharp dumbbell-shaped or micro-knife-shaped shape needs to rely on external force to swing or rotate, and the surface morphology is changed by adjusting the contact angle and contact area with the droplet to guide the droplet. However, the above-mentioned dynamic movement mode is completely dependent on external drive, so it is easy to cause mechanical fatigue problems, which in turn affects the accuracy of manipulation. In the present technical solution, the exposed area on the surface of the substrate adopts staggered isosceles triangles, so that the magnetic control layer presents a static geometric pattern. Only by relying on the sharp increase in surface energy caused by the sharp shape of the vertex angle, the transmission and movement of the droplets can be effectively guided, avoiding the problem of reduced droplet manipulation accuracy caused by the exposed area on the surface of the substrate being a sharp dumbbell-shaped or micro-knife-shaped, thereby ensuring the accuracy of the droplet transmission path.

[0050] Further, the mask on the surface of the substrate is removed and cleaned. After removing the mask, a magnetron layer of the desired pattern is formed, which is conducive to further processing or treatment of the magnetron layer. In addition, the cleaning step is conducive to forming a good bond between the magnetron layer and the substrate, thereby improving the adhesion and stability of the magnetron layer, thereby improving the working efficiency, stability and service life of the device. It should be noted that in step D, the specific step of cleaning is to use deionized water for cleaning.

[0051] Again, although the fluorine-doped graphene in the magnetron layer can reduce the surface energy, the hydrophobicity of the fluorine-doped graphene in the magnetron layer alone is not enough to completely eliminate the friction between the droplets and the device surface during droplet manipulation, and it is impossible to ensure that the droplets move smoothly and stably on the device surface. Therefore, in the present technical solution, the substrate with the magnetron layer in step E is immersed in silicone oil, taken out and suspended to stand, so that a lubricating layer is deposited on the surface of the substrate with the magnetron layer. The lubricating layer can further reduce the friction between the droplets and the device surface, so that the droplets can move controllably along the transmission path on the device surface under the dual effects of the surface energy gradient or the surface energy gradient and the micro-roughness gradient, thereby improving the smoothness and precision of droplet manipulation. In addition, suspension and stillness can allow excess silicone oil to flow out from the surface of the lubricating layer, ensuring the uniformity of the lubricating layer.

[0052] Finally, if the material of the substrate is magnetic, it will interfere with the effect of the external magnetic field, affecting the manipulation of the droplets, thereby affecting the accuracy and controllability of the droplet transmission path; in addition, a high temperature environment will be generated during the pulse current processing process. If the material of the substrate has poor high temperature resistance, thermal expansion or material deformation may occur, thereby destroying the device structure. Therefore, in this technical solution, the material of the substrate is limited to a non-magnetic and high temperature resistant material, so as to ensure the integrity of the device structure and the accuracy and controllability of the droplet transmission path.

[0053] It should be noted that the spacing between adjacent isosceles triangles in the exposed area of ​​the substrate surface of the present technical solution can be designed according to the diameter and surface tension of the droplets actually required to be transported. Generally, the spacing between adjacent isosceles triangles is ≤ 1 / 2 of the droplet diameter, which will not be described in detail here.

[0054] Preferably, the silicone oil includes any one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, ethyl hydrogen silicone oil, methyl phenyl silicone oil, methyl chlorophenyl silicone oil, methyl ethoxy silicone oil, methyl trifluoropropyl silicone oil and methyl vinyl silicone oil.

[0055] Further explanation: in step A, the vertex angle of the isosceles triangle is 20-45°.

[0056] If the vertex angle of the isosceles triangle is too small or too sharp, the droplets may be trapped in the vertex area and not be able to move smoothly to the adjacent bottom edge, causing the transmission process to be blocked; if the vertex angle of the isosceles triangle is too large, the guiding effect of the droplets at the vertex is weakened, the degree of increase in surface energy is limited, the controllability of the droplets decreases, and they are prone to spread irregularly along the surface of the isosceles triangle. Therefore, the technical solution optimizes the angle of the vertex angle of the isosceles triangle to ensure the controllability and accuracy of the droplet transmission path.

[0057] Further, in step B, calculated by mass ratio, the mixing ratio of the anhydrous ferric chloride to the deionized water is (0.9-1.1):2.

[0058] If the ratio of anhydrous ferric chloride to deionized water is too small, that is, the content of anhydrous ferric chloride is too little, the device's response to the magnetic field will be weakened, affecting its accuracy in controlling droplets; if the ratio of anhydrous ferric chloride to deionized water is too large, that is, the content of anhydrous ferric chloride is too high, although the device will be more sensitive to the magnetic field, it will cause the overall structure of the device to become brittle, the device's reversible deformation ability will be reduced, and it will be more prone to structural damage.

[0059] Further, in step B, calculated by mass ratio, the mixing ratio of the ferric chloride solution, the carbon-based raw material and the fluorine source raw material is (0.45-0.55):1:(0.1-0.12).

[0060] If the proportion of ferric chloride solution is too large, the ferric chloride-carbon-based-fluorine source complex will be too dilute, the fluidity will increase, and it will not be able to be well fixed on the substrate surface for patterning processing; if the proportion of ferric chloride solution is too small, the ferric chloride-carbon-based-fluorine source complex will be dry, and it will not be easy to evenly apply and disperse on the substrate surface, resulting in poor thickness uniformity of the obtained device, affecting the accuracy of its control over the droplets.

[0061] Further, within a certain range, the conductivity of the carbon-based raw material increases with the increase of its density. However, when the density of the carbon-based raw material increases to a certain extent, due to the close packing between particles, the electron transmission path may be blocked, which reduces the conductivity instead. In this technical solution, the area where the substrate can be coated with the ferric chloride-carbon-based-fluorine source composite is fixed. If there are too many carbon-based raw materials, the density of the carbon-based raw materials in this area will increase, resulting in the overall resistance of the ferric chloride-carbon-based-fluorine source composite being too large, affecting the conversion rate of the carbon-based raw materials into graphene, thereby reducing the performance of the device.

[0062] Furthermore, if the proportion of fluorine source raw materials is too large, it will affect the uniformity of the distribution of the fluorine source raw materials on the graphene surface, causing an imbalance in the surface energy gradient of the device and reducing the accuracy of droplet manipulation; if the proportion of fluorine source raw materials is too small, the hydrophobicity of the device surface will be reduced, affecting the rolling and manipulation performance of the droplets, making it difficult for the droplets to move quickly, causing the droplets to be locally retained on the device surface.

[0063] Further explanation: in step D, the voltage of the pulse current is 120-140V, the current is 180-200A, and the processing time is 8-10s.

[0064] By limiting the processing parameters of the pulse current, it is beneficial to convert the ferric chloride-carbon-fluorine source complex into a fluorine-doped graphene-ferroferric oxide combination in one step, thereby improving the quality of the device and further simplifying the preparation method.

[0065] Further, in step E, the thickness of the magnetron layer is 0.3-0.5 mm.

[0066] The magnetron layer is obtained by pulse processing of fluorine-doped graphene-iron tetroxide. If the thickness of the magnetron layer exceeds the appropriate range, the thickness of the fluorine-doped graphene-iron tetroxide will also be thicker. The thicker fluorine-doped graphene-iron tetroxide will hinder the effective transfer of heat, making it difficult for the interior of the fluorine-doped graphene-iron tetroxide to quickly reach the required processing temperature, thereby affecting the uniformity and stability of the magnetron layer.

[0067] Further, in step F, the soaking time is 4 to 6 minutes; the hanging and standing time is 10 to 15 minutes.

[0068] If the immersion time is too short, the silicone oil will not easily cover the surface of the device evenly, resulting in insufficient lubricity in some areas of the device; if the immersion time is too long, the silicone oil will excessively penetrate into the magnetron layer, resulting in a decrease in the cohesive force between the raw materials in the magnetron layer, thereby increasing the adhesion between the magnetron layer and the droplets, which is not conducive to the precise control of the droplets.

[0069] If the suspension time is too short, too much silicone oil may remain on the surface of the device, resulting in poor thickness uniformity of the device and reduced controllability of the device over droplets. If the suspension time is too long, it can easily lead to a decrease in production efficiency.

[0070] Further description, in step A, the substrate includes any one of a glass substrate, a silicon wafer and an alumina ceramic.

[0071] Glass substrates, silicon wafers and alumina ceramics are non-magnetic and have good high temperature resistance. Therefore, in the technical solution, the substrate is preferably any one of glass substrates, silicon wafers and alumina ceramics, which is conducive to ensuring the performance of the product.

[0072] Further, in step B, the carbon-based raw material includes any one or more combinations of carbon black, coal powder, lignin and corn silk;

[0073] The fluorine source raw material includes any one of fluorinated graphite, perfluorooctanoic acid, perfluorohexyl sulfonic acid and polytetrafluoroethylene.

[0074] Carbon black, coal powder, lignin and corn silk can all be converted into graphene under pulsed current processing conditions, which helps to ensure the performance of the product.

[0075] Furthermore, when the fluorine source reacts with the magnetic material ferroferric oxide, not only will some of the fluorine atoms be unable to be incorporated into the graphene, which will greatly reduce the hydrophobicity of the device and affect the accuracy of droplet transmission; it will also cause the magnetism of the device to decrease, which also affects the accuracy of droplet transmission. Therefore, in this technical solution, raw materials such as fluorinated graphite, perfluorooctanoic acid, perfluorohexane sulfonic acid and polytetrafluoroethylene that do not react with the magnetic material ferroferric oxide at high temperatures are used to ensure the accuracy of droplet transmission.

[0076] A device with a controllable droplet transport path is prepared using the above-mentioned method for preparing a device with a controllable droplet transport path.

[0077] This technical solution also proposes a device with controllable droplet transport path prepared using a preparation method with controllable precision of droplet transport path, which can precisely control droplets and flexibly and stably transport them, thereby achieving controllability and precision of the droplet transport path, greatly meeting practical application needs.

[0078] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0079] Example 1

[0080] A. Partially covering the surface of the glass substrate with a mask; wherein the surface of the glass substrate includes a mask-covered area and an exposed area, the exposed area is in the shape of an isosceles triangle with a vertex angle of 20°, and a plurality of isosceles triangles are staggered and arranged at equal intervals;

[0081] B. Dissolve anhydrous ferric chloride in deionized water and stir to obtain a ferric chloride solution; mix the ferric chloride solution, carbon black and perfluorooctanoic acid to obtain a ferric chloride-carbon black-perfluorooctanoic acid complex; calculated by mass ratio, the mixing ratio of anhydrous ferric chloride and deionized water is 1:2; calculated by mass ratio, the mixing ratio of the ferric chloride solution, carbon black and perfluorooctanoic acid is 0.5:1:0.1;

[0082] C. applying the ferric chloride-carbon black-perfluorooctanoic acid complex prepared in step B evenly to the surface of the exposed area of ​​the glass substrate prepared in step A to obtain a glass substrate having the ferric chloride-carbon-based-fluorine source complex attached to the surface;

[0083] D. Processing the ferric chloride-carbon-based-fluorine source complex on the surface of the glass substrate in step C for 8 seconds using a pulse current of 120 V and 180 A to obtain a glass substrate with a fluorine-doped graphene-ferroferric oxide complex attached to the surface;

[0084] E. removing the mask on the surface of the glass substrate in step D and cleaning it to obtain a glass substrate with a magnetron layer; wherein the thickness of the magnetron layer is 0.3 mm; and the magnetron layer is a fluorine-doped graphene-ferroferric oxide combination;

[0085] F. Soak the glass substrate with the magnetron layer in step E in methyl silicone oil for 4 minutes, take it out and hang it to stand for 15 minutes, and then deposit a lubricating layer on the surface of the glass substrate with the magnetron layer to obtain a device with controllable droplet transport path.

[0086] The device with controllable droplet transport path obtained in Example 1 is placed in a magnetic field, droplets are placed at the top corner or bottom edge of the outer surface of the device with controllable droplet transport path, and the magnetic field strength and direction are adjusted during the droplet transmission process to control the droplets to be transmitted along a preset path, and the deviation of the droplet transmission path is observed with a microscope.

[0087] The results show that the device with controllable droplet transport path obtained in Example 1 can control the droplet transport path to be transmitted along a preset path, and the droplets have basically no deviation during the transmission process, and the controllability and accuracy of the droplet transmission path are high.

[0088] Example 2

[0089] A. Partially covering the surface of the silicon wafer with a mask; wherein the surface of the glass substrate includes a mask-covered area and an exposed area, the exposed area is in the shape of an isosceles triangle with a vertex angle of 30°, and a plurality of isosceles triangles are staggered and arranged at equal intervals;

[0090] B. dissolving anhydrous ferric chloride in deionized water and stirring to obtain a ferric chloride solution; mixing the ferric chloride solution, coal powder and perfluorohexane sulfonic acid to obtain a ferric chloride-coal powder-perfluorohexane sulfonic acid complex; the mixing ratio of anhydrous ferric chloride and deionized water is 0.9:2; the mixing ratio of ferric chloride solution, coal powder and perfluorohexane sulfonic acid is 0.45:1:0.12 according to the mass ratio;

[0091] C. applying the ferric chloride-coal powder-perfluorohexane sulfonic acid complex prepared in step B evenly to the surface of the exposed area of ​​the silicon wafer prepared in step A to obtain a silicon wafer with the ferric chloride-carbon-based-fluorine source complex attached to the surface;

[0092] D. Processing the ferric chloride-carbon-based-fluorine source complex on the surface of the silicon wafer in step C for 10 seconds using a pulse current of 130 V and 200 A to obtain a silicon wafer with a fluorine-doped graphene-ferroferric oxide complex attached to the surface;

[0093] E. removing the mask on the surface of the silicon wafer in step D and cleaning it to obtain a silicon wafer with a magnetron layer; wherein the thickness of the magnetron layer is 0.5 mm; and the magnetron layer is a fluorine-doped graphene-ferroferric oxide combination;

[0094] F. Soak the silicon wafer with the magnetron layer in step E in phenyl silicone oil for 6 minutes, take it out and hang it to stand for 15 minutes, and then deposit it on the surface of the silicon wafer with the magnetron layer to obtain a device with controllable droplet transport path.

[0095] The device with controllable droplet transport path obtained in Example 2 is placed in a magnetic field, droplets are placed at the top corner or bottom edge of the outer surface of the device with controllable droplet transport path, and the magnetic field strength and direction are adjusted during the droplet transmission process to control the droplets to be transmitted along a preset path, and the deviation of the droplet transmission path is observed with a microscope.

[0096] The results show that the device with controllable droplet transport path obtained in Example 2 can control the droplet transport path to be transmitted along a preset path, and the droplets have basically no deviation during the transmission process, and the controllability and accuracy of the droplet transmission path are high.

[0097] Example 3

[0098] A. A mask is partially covered on the surface of the alumina ceramic; wherein the surface of the glass substrate includes a mask-covered area and an exposed area, the exposed area is in the shape of an isosceles triangle with a vertex angle of 45°, and a plurality of isosceles triangles are staggered and arranged at equal intervals;

[0099] B. Dissolve anhydrous ferric chloride in deionized water and stir to obtain a ferric chloride solution; mix the ferric chloride solution with lignin and polytetrafluoroethylene to obtain a ferric chloride-lignin-polytetrafluoroethylene composite; the mixing ratio of anhydrous ferric chloride and deionized water is 1.1:2 according to the mass ratio; the mixing ratio of ferric chloride solution, carbon black and perfluorooctanoic acid is 0.55:1:0.1 according to the mass ratio;

[0100] C. evenly applying the ferric chloride-lignin-polytetrafluoroethylene composite of step B to the surface of the exposed area of ​​the alumina ceramic in step A to obtain an alumina ceramic with the ferric chloride-lignin-polytetrafluoroethylene composite attached to the surface;

[0101] D. Processing the ferric chloride-carbon-based-fluorine source complex on the surface of the alumina ceramic in step C for 9 seconds using a pulse current of 140 V and 190 A to obtain an alumina ceramic with a fluorine-doped graphene-ferroferric oxide complex attached to the surface;

[0102] E. removing the mask on the surface of the alumina ceramic in step D and cleaning it to obtain an alumina ceramic with a magnetron layer; wherein the thickness of the magnetron layer is 0.4 mm; and the magnetron layer is a fluorine-doped graphene-ferroferric oxide combination;

[0103] F. Soak the alumina ceramic with a magnetron layer in step E in ethyl silicone oil for 5 minutes, take it out and suspend it for 12 minutes, and then deposit a lubricating layer on the surface of the alumina ceramic with a magnetron layer to obtain a device with controllable droplet transport path.

[0104] The device with controllable droplet transport path obtained in Example 3 is placed in a magnetic field, droplets are placed at the top corner or bottom edge of the outer surface of the device with controllable droplet transport path, and the magnetic field strength and direction are adjusted during the droplet transmission process to control the droplets to be transmitted along a preset path, and the deviation of the droplet transmission path is observed with a microscope.

[0105] The results show that the device with controllable droplet transport path obtained in Example 3 can control the droplet transport path to be transmitted along a preset path, and the droplets have basically no deviation during the transmission process, and the controllability and accuracy of the droplet transmission path are high.

[0106] Comparative Example 1

[0107] Except that in step A, the substrate is a substrate without a mask, the remaining steps are the same as those in embodiment 1.

[0108] The device with controllable droplet transport path obtained in Comparative Example 1 is placed in a magnetic field, droplets are placed at any position of the device with controllable droplet transport path, and the magnetic field strength is adjusted during the droplet transmission process to manipulate the droplets to be transmitted along a preset path, and the droplet transmission path and stability are observed with a microscope.

[0109] The results show that although the device with controllable droplet transport path obtained in Example 1 can control the droplet transport path to transport along the preset path, the controllability and accuracy of the droplet transport path are poor.

[0110] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a device with a controllable droplet transport path, characterized in that: The following steps are involved: A. Covering a part of the surface of the substrate with a mask; wherein the surface of the substrate includes a mask-covered area and an exposed area, the exposed area is in the shape of an isosceles triangle, and a plurality of the isosceles triangles are arranged in an interlaced and equidistant manner, and the substrate is made of a high-temperature resistant non-magnetic material; B. dissolving anhydrous ferric chloride in deionized water and stirring to obtain a ferric chloride solution; mixing the ferric chloride solution with a carbon-based raw material and a fluorine source raw material to obtain a ferric chloride-carbon-based-fluorine source composite; C. applying the ferric chloride-carbon-based-fluorine source composite of step B evenly to the surface of the exposed area of ​​the substrate in step A to obtain a substrate with the ferric chloride-carbon-based-fluorine source composite attached to the surface; D. processing the ferric chloride-carbon-based-fluorine source complex on the surface of the substrate in step C by using a pulse current to obtain a substrate with a fluorine-doped graphene-ferroferric oxide complex attached to the surface; E. removing the mask on the surface of the substrate in step D and cleaning it to obtain a substrate having a magnetron layer; wherein the magnetron layer is a fluorine-doped graphene-ferroferric oxide combination; F. Immerse the substrate with the magnetron layer in step E in silicone oil, take it out and suspend it for standing, and then deposit a lubricating layer on the surface of the substrate with the magnetron layer to obtain a device with a controllable droplet transport path.

2. The method for preparing a device with controllable droplet transport path according to claim 1, characterized in that: In step A, the vertex angle of the isosceles triangle is 20-45°.

3. The method for preparing a device with controllable droplet transport path according to claim 1, characterized in that: In step B, the mixing ratio of the anhydrous ferric chloride and the deionized water is (0.9-1.1):2 calculated by mass ratio.

4. The method for preparing a device with controllable droplet transport path according to claim 1, characterized in that: In step B, calculated by mass ratio, the mixing ratio of the ferric chloride solution, the carbon-based raw material and the fluorine source raw material is (0.45-0.55):1:(0.1-0.12).

5. The method for preparing a device with controllable droplet transport path according to claim 1, characterized in that: In step D, the voltage of the pulse current is 120-140V, the current is 180-200A, and the processing time is 8-10s.

6. The method for preparing a device with controllable droplet transport path according to claim 1, characterized in that: In step E, the thickness of the magnetron layer is 0.3-0.5 mm.

7. The method for preparing a device with controllable droplet transport path according to claim 1, characterized in that: In step F, the soaking time is 4 to 6 minutes; the hanging and standing time is 10 to 15 minutes.

8. The method for preparing a device with controllable droplet transport path according to claim 1, characterized in that: In step A, the substrate includes any one of a glass substrate, a silicon wafer and an alumina ceramic.

9. The method for preparing a device with controllable droplet transport path according to claim 1, characterized in that: In step B, the carbon-based raw material includes any one or more combinations of carbon black, coal powder, lignin and corn silk; The fluorine source raw material includes any one of fluorinated graphite, perfluorooctanoic acid, perfluorohexyl sulfonic acid and polytetrafluoroethylene.

10. A device with a controllable droplet transport path, characterized in that: The device is prepared using the method for preparing a device with a controllable droplet transport path as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Functional interface with liquid self-driven directed transportation ability, and manufacturing method and application thereof

    CN106944165A

  • Photothermal directional control elastic superhydrophobic surface liquid drop migration device and using method thereof

    CN109810515A

  • Magnetic control molecular comb method for single molecule DNA stretching

    CN113514297A

  • Magnetic control graphene-based micro-nano motor and preparation method thereof

    CN114643043A

  • Flexible film with controllable droplet transport path and preparation method and application thereof

    CN115386110A